Analisis Investasi Emas Online pada Aplikasi Dinaran berdasarkan Tinjauan Fatwa MUI No.77/DSN-MUI/V/2010 - Chaniago, Akbar; Muhibbussabry (Jurnal Alwatzikhoebillah : Kajian Islam, Pendidikan, Ekonomi, Humaniora, 2026)
This study aims to examine the conformity of digital gold investment practices of Dinaran application with the provisions of DSN-MUI Fatwa No. 77/DSN-MUI/V/2010 and the fundamental principles of Islamic jurisprudence in mu‘āmalah. This research is motivated by the rapid growth of digital platforms for gold investment in Indonesia, which offer ease of access, transactional flexibility, and operational efficiency. Nevertheless, such developments simultaneously raise significant sharia legal concerns, given that gold constitutes a ribāwī commodity that requires contractual certainty, transparent pricing, and legitimate possession in every transaction. The study employs an empirical legal research approach combined with a normative analysis grounded in fiqh al-mu‘āmalah. Primary data were collected through direct observation of the operational mechanisms of the Dinaran platform, while secondary data were derived from DSN-MUI fatwas, relevant regulatory frameworks, and scholarly literature. The findings indicate that the digital gold purchasing process on the Dinaran application satisfies the principles of price clarity and object specification. Therefore, value fluctuations resulting from market price movements cannot be classified as ribā, but rather represent a reasonable market risk inherent in gold trading as a commodity. However, with regard to the mechanism for withdrawing physical gold, the fulfillment of the qabḍ element tends to take the form of qabḍ ḥukmī, as the delivery process involves a time delay and limited transparency concerning the existence of gold as the underlying asset. Gold investment practices within the Dinaran application may be considered permissible within sharia boundaries, although further improvements are necessary to enhance ownership transparency and ensure procedural certainty in the physical delivery of gold.